Ministerial Decree No. 137/2013 Amending Ministerial Decree No. 231/2008 on the determination of brokerage commissions, securities lists fees, and service charges for stock exchange transactions / translated by The middle east library for economic services. - The middle east library for economic services, translator. (2025)
The Ministry of Investment Decree No. 137 of the Year 2013 وزارة الاستثمار قرار رقم 137 لسنة 2013